PENGARUH MODEL THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Pranashanti Pranashanti; Hamdani Hamdani; Endang Uliyanti (Universitas Tanjungpura, 2019)
AbstractThis study aims to analyze the influence of the application of the think pair share model to the mathematics learning outcomes of grade V students of Pontianak city 17th elementary school. The methodology that was used for this study was the experimental methods. As for the population in this study was 90 students from the grade V in the 17th elementary school. The sample in this study are all the students of grade VC with a number of 32 students as an experiment class and students of VA with a number of 29 students as control class. The data collection techniques that was used were a measurement techniques. Based on the analysis results that were obtained tcount (2,041) > ttable (1,671) thus, the alternative hypothesis is accepted. Therefore, it can be concluded that there are differences in learning outcomes between experiment class and control class. Based on the calculation of the effect size were obtained as much as 0,38 with moderate criteria. It can be conclude that learning by applying think pair share model has a moderate effect on student learning outcomes in grade V of Pontianak city 17th elementary schools.Keywords: Cooperatif Learning, Learning Outcomes, Think Pair Share Model.